Delivering the Aichi target 11: challenges and opportunities for marine areas beyond national jurisdiction. Issue 2 (November 2014) - Rochette, Julien; Gjerde, Kristina; Druel, Elisabeth; Ardron, Jeff A.; Craw, Alicia; Halpin, Patrick; Pendleton, Linwood; Teleki, Kristian; Cleary, Jesse
ABSTRACT In 2010, Contracting Parties to the Convention on Biological Diversity adopted the so‐called 'Aichi targets' in order to achieve global biodiversity conservation. Target 11 specifically provides that 'by 2020 (…) at least 10 per cent of coastal and marine areas (…) are conserved through effectively and equitably managed, ecologically representative and well‐connected systems of protected areas and other effective area‐based conservation measures'. This objective is currently far from being reached since less than 3% of the ocean has been designated as marine protected areas (MPAs). In areas beyond national jurisdiction (ABNJ) in particular, with less than 0.5% protected, there is no mechanism aimed at creating internationally‐recognized MPAs and the initiatives launched by regional organizations, although promising, have limitations. ABNJ are nevertheless facing increasing human pressures and it is therefore appropriate and pressing to designate a comprehensive and representative network of MPAs in these areas. This paper analyses the current efforts conducted to better conserve marine biodiversity in ABNJ and identifies enabling conditions for meeting the Aichi Target 11. Copyright © 2014 John Wiley & Sons, Ltd.